Design and comparative analysis of different pricing mechanisms and energy allocation policies for energy trading - Lim, Jerand Ze Hui (Nanyang Technological University, 2022)
As a result of global warming, a transition from fossil fuel to zero-carbon emissions generation is now required for a healthy and eco-friendly society. As a result, the dependency on fossil fuels, natural gas, and coals to produce electricity will be minimized. Peer-to-peer (P2P) energy trading has been proposed as a solution to this problem. Consumers and prosumers transfer energy without the need for a mediator in the P2P energy trading concept. As a key component of boosting renewable energy and system flexibility for a low-carbon energy transition, peer-to-peer energy trading is crucial. The Final Year Project (FYP) outlines the plan to create and propose an effective pricing and allocation policy technique for P2P trading in this final report. This increases the social welfare of all the participants in energy trading market.